Економічна характеристика продукції та послуг підприємств залізничного транспорту - Орлов, В.М. (Економічні інновації, 2012)
Рассматриваются основные положения по определению понятия продукции, услуг предоставляемых предприятиями железнодорожного транспорта, их экономическая характеристика. In this article principal regulations on definition of production and services notions which are offered by railway transport enterprises to consumers are considered on the basis of generalization and analysis of normative and legal documents.
Services definition according to 3279-95 National Standard of Ukraine, their list according to the “List of work and services” that relate to main activities of a railway transport have been considered. We have determined the lack of transport services and transport production notions in this list. This is reason we have based the notions of transport production as a final result of transport branch production, that is cargo and passenger transport, and of a transport service as activities of a business entity that is directed to the change of location of people and cargo lots that are accomplished according to a preliminary agreement between a service provider and a client.
We have given an economic characteristics of transport service and production, their peculiarity including non-material character (that is impossibility to keep, accumulate and store), special requirements to the quality of a provided service, and simultaneity of provision and consumption (a result) etc.
Enumerated peculiarities and characteristics of production and services are specialties of a created product by railway transport enterprises and the require to be properly discussed and to determine their place in normative and legal documents (as an index system when evaluating the work of railway transport enterprises). Розглядаються основні положення щодо визначення понять продукції, послуг надаваних підприємствами залізничного транспорту, їх економічна характеристика.